Epidemiologic characteristics, the length of hospital stay, and mortality of patients with organophosphate poisoning: A systematic review - Janet Alva; Elsa Sanatombi Devi; Ramesh Chandrababu; Julliet Abraham; Jayraj Mymbilly Balakrishnan (Clinical Epidemiology and Global Health)
Background: Organophosphate poisoning is continuing to be a rising cause for the presentation to emergency department and admission to the Intensive Care Units in India. Objective: The objective of this review was to quantitatively synthesize the data to identify the epidemiologic characteristics, the length of hospital stays, and mortality of patients with organophosphate poisoning. Methods: A systematic review of the scientific studies published between 2010 and 2022 was carried out. With the help of comprehensive search strategy, 15 out of 112 articles from databases like CINAHL, EBSCO, Scopus, PUBMED, ProQuest, Web of Science, and Central were retrieved. The Joanna Briggs Institute (JBI) guidelines was adopted and reported using the PRISMA guidelines. Results: The total participants reported by the current review were 28,593 patients. This review also highlighted that the mean age of participants was 42.22 ± 9.29 years and the mean duration of arrival to hospital was 5.97 ± 2.48 h. Majority of the participants reported were male 20,127 (70.4 %). It was also reported that 3331(11.6 %) patients developed complications and 71.7 % (2387) patients were on mechanical ventilation. This review also reported that 6732 (23.5 %) patients were discharged after recovery while 1059 (3.7 %) patients succumbed during treatment. Conclusion: The delay in hospital arrival of the patient worsens the condition of organophosphate poisoned patient resulting in serious complications, prolonged hospital stay and even increases the caregiver burden. The mass awareness to be created for the public to ensure the victim reaches the hospital for immediate medical care to prevent mortality and minimize morbidity.